ANALISIS MAKRO EKONOMI TERHADAP CADANGAN DEVISA INDONESIA (MELALUI PENDEKATAN MONETER) - Novri Candra; Idris Idris; Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aimed to analyze the change in foreign exchange reserves which are affected by the state of national income, exchange rates, interest rates and inflation. This study was conducted to see the effect of the independent variable on the dependent variable in the long term and short term. The method used is the Error Correction Model (ECM). This study shows that the long-term effects of the variables national income and the exchange rate has a significant positive effect on foreign exchange reserves, while in the short term have a negative effect but not significant. Variable interest rates on long-term have a positive effect but not significant and in the short term have a significant negative effect on foreign exchange reserves. Variable inflation in the long term and short term no significant effect on the foreign exchange reserves. Results Error Correction Term (ECT) in this study amounted to 1,065, which means that in the short-term foreign exchange reserves will undergo considerable change and requires quite a long time to come back into balance.Keyword : Reserves, National Income, Exchange Rates, Interest Rates and Inflation ECM, ECT